Faith, Reason, & Earth History : A Pradigm of Earth and Biological Origins by Intelligent Design - Brand, Leonard (Andews University Press, 2009)
Faith, Reason, and Earth History presents Leonard Brand's argument for constructive thinking about origins and earth history in the context of Scripture, showing readers how to analyze available scientific data and approach unsolved problems. Faith does not need to fear the data, but can contribute to progress in understanding earth history within the context of God's Word while still being honest about unanswered questions. In this patient explanation of the mission of science, the author models his conviction that above all, it is essential that we treat each other with respect, even if we disagree on fundamental issues. The original edition of this work (1997) was one of the first books on this topic written from the point of view of an experienced research scientist. A career biologist, paleontologist, and teacher, Brand brings to this well-illustrated book a rich assortment of practical scientific examples. This thoughtful and rigorous presentation makes Brand's landmark work highly useful both as a college-level text and as an easily accessible treatment for the educated lay person.